Bench-to-Bedside and Bedside Back to the Bench; Seeking a Better Understanding of the Acute Pathophysiological Process in Severe Traumatic Brain Injury - Agoston, Denes V. (Frontiers in Neurology, 2015)
Despite substantial investments, traumatic brain injury (TBI) remains one of the major disorders that lack specific pharmacotherapy. To a substantial degree this situation is due to lack of understanding of the pathophysiological process of the disease. Experimental TBI research offers controlled, rapid and cost-effective means to identify the pathophysiology but translating experimental findings into clinical practice can be further improved by using the same or similar outcome measures and clinically relevant time points. The pathophysiology during the acute phase of severe TBI is especially poorly understood. In this Minireview, I discuss the some of the incongruences between current clinical practices and needs versus information provided by experimental TBI research as well as the benefits of designing animal experiments with translation into clinical practice in mind.